STRUCTURE AND LUMINESCENCE OF Bi2Zr2O7:Eu3+,Tb3+ RED PHOSPHORS FOR WHITE LIGHT-EMITTING DIODES - Van Hai, Nguyen; Thi Ngoc Linh, Vu; Van Cuu, Ho; Viet Long, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
In this study, Eu3+ and Tb3+ co-doped Bi2Zr2O7 (BZO) pyrochlore phosphors were successfully synthesized via a combustion method at 600°C. The crystal structure, elemental composition, morphology, luminescent characteristics, and energy transfer behavior were systematically investigated. Powder X-ray diffraction (XRD) analysis confirmed that all synthesized samples exhibited a pure single-phase pyrochlore structure, with Eu3+ and Tb3+ ions efficiently incorporated into the host lattice. Under blue light excitation at 466 nm, BZO:Eu3+,Tb3+ phosphors exhibited relatively strong red emission. Efficient energy transfer from Tb³⁺ to Eu³⁺ was observed, leading to a significant enhancement in red luminescence. Furthermore, the obtained phosphors demonstrated color purities approaching 90%. These results suggest that Tb3+ ions effectively act as sensitizers to Eu3+, and the new kinds of BZO:Eu3+,Tb3+ phosphors hold great potential for application in blue-excited white light-emitting diodes (WLEDs).